Development of MALDI-TOF mass spectrometry for the identification of lice isolated from farm animals - Basma Ouarti; Maureen Laroche; Souad Righi; Mohamed Nadir Meguini; Ahmed Benakhla; Didier Raoul; Philippe Parola (EDP Sciences, 2020)
Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) is now routinely used for the rapid identification of microorganisms isolated from clinical samples and has been recently successfully applied to the identification of arthropods. In the present study, this proteomics tool was used to identify lice collected from livestock and poultry in Algeria. The MALDI-TOF MS spectra of 408 adult specimens were measured for 14 species, including Bovicola bovis, B. ovis, B. caprae, Haematopinus eurysternus, Linognathus africanus, L. vituli, Solenopotes capillatus, Menacanthus stramineus, Menopon gallinae, Chelopistes meleagridis, Goniocotes gallinae, Goniodes gigas, Lipeurus caponis and laboratory reared Pediculus humanus corporis. Good quality spectra were obtained for 305 samples. Spectral analysis revealed intra-species reproducibility and inter-species specificity that were consistent with the morphological classification. A blind test of 248 specimens was performed against the in-lab database upgraded with new spectra and validated using molecular tools. With identification percentages ranging from 76% to 100% alongside high identification scores (mean = 2.115), this study proposes MALDI-TOF MS as an effective tool for discriminating lice species.